Tracking the Creativity of Autobiography and Biography Text Through Poster Media for Higher Education - Torkis Lubis; Zainul Arifin; Suci Ramadhanti Febriani; Prayoga Saputra; Desriliwa Ade Mela; Kddour Geuttaoui Bedra (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This research aims to analyze students' creativity in writing autobiography and biography texts in Arabic using poster media in higher education. Researchers used a qualitative approach with a case study method on 35 students. Data collection techniques used interviews, documentation and observation in Arabic writing skills learning activities, while the data analysis techniques used included triangulation of data sources identified through three stages, namely data collection, data reduction, data presentation and drawing conclusions. The research results show that: 1) Student creativity in writing autobiographical and biographical texts using posters is more varied with the choice of colors, images and identification of introductory texts, experiences and life learning; 2) the sentence structure used consists of five structures, namely the structure of verbs, nouns, adverbial attributes, properties and prepositions. Research findings show that the use of poster media in learning writing skills is able to develop creativity and a variety of sentence structures. This research is limited to only two texts, so the researcher recommends further research to analyze a variety of other texts using poster media and more varied research methods.